2018
DOI: 10.1159/000494537
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Polyethylene-Induced Osteolysis via Repressing NF-κB Signaling Pathway Activation

Abstract: Background/Aims: Aseptic loosening is a common reason for failed artificial hip replacement after total hip arthroplasty. Aseptic loosening is mostly the result of wear debris that causes osteolysis and weakens the structures that support the prosthesis. Wear debris plays a crucial role in osteolysis during the loosening process, and polyethylene (PE) particles are found as wear debris more frequently than any other type of particle. In the absence of effective therapeutic agents, osteolysis has been hard to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…After RANKL treatment, OC differentiation of RAW 264.7 cells produced large, round, and red-stained multinucleated OCs in the PBS group ( Figure 3D). In contrast, after curcumin treatment, the number of mature TRAP-positive OCs decreased (Figure 2E, p < 0.05), signifying that curcumin could attenuate OC formation, which was consistent with our previously study (An et al, 2018). Similarly, the number of TRAP-positive OCs significantly decreased after ZSCNP treatment ( Figure 3E, p < 0.05), indicating that curcumin in ZSCNPs could effectively reduce OC formation, which was in line with the in vitro curcumin release experiment in this study.…”
Section: Cell Experiments Withsupporting
confidence: 92%
See 4 more Smart Citations
“…After RANKL treatment, OC differentiation of RAW 264.7 cells produced large, round, and red-stained multinucleated OCs in the PBS group ( Figure 3D). In contrast, after curcumin treatment, the number of mature TRAP-positive OCs decreased (Figure 2E, p < 0.05), signifying that curcumin could attenuate OC formation, which was consistent with our previously study (An et al, 2018). Similarly, the number of TRAP-positive OCs significantly decreased after ZSCNP treatment ( Figure 3E, p < 0.05), indicating that curcumin in ZSCNPs could effectively reduce OC formation, which was in line with the in vitro curcumin release experiment in this study.…”
Section: Cell Experiments Withsupporting
confidence: 92%
“…Studies have shown that inhibiting the activity of IKK can lead to repressing the phosphorylation of the p65 subunit of NF-kB, thereby inhibiting the nuclear ectopic of NF-kB to suppress downstream pathways (Fiume et al, 2015;Pontoriero et al, 2019). Furthermore, our group verified that curcumin can inhibit the entire NF-κB activation process by inhibiting the effect of IKK, preventing polyethylene (PE)-induced osteolysis and bone loss, and repressing the RANK/c-Fos/nuclear factor of activated T cells cytoplasmic 1 (NFATc1) signaling pathway (An et al, 2018). However, to the best of our knowledge, no studies have reported on the benefits of curcumin-loaded NPs in inhibiting PE-induced osteolysis.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations